Der Alto Tapajóz-Cururú: Erläuterungen zu einer Stromkarte Brasiliens - Zimmermann, Josef (ERDKUNDE, 1957)
The accompanying river map is based on the records of the missionaries of the Missao S. Francisco at the Cururu River, and on the observations of the author during his journey to the Munduruku Indians in spring 1952. The name Alto Tapajoz (Upper Tapajoz) is used for the section from the confluence of the Juruena and the Teles Pires, or Sao Manuel, to the rapids of Sao Luiz; it is that section of the river which studded with numerous rapids and shallows makes navigation impossible for larger vessels and permits access only to smaller motor launches, the typical lanchas a motor. The seasonal rise and fall of the river corresponding to the rainy and dry halves of the year exerts great influence on the river bed and the banks. During rising water, in addition to downcutting, lateral erosion increases particularly; when the flood waters recede the downcutting force becomes the relatively more pronounced. The tendency of the river towards lateral erosion is, in addition to the floods, also increased by the great number of shoals of hard rocks and by narrows which again and again act as barrages. A consequence of this is an almost uninterrupted sequence of concave banks or garlands on both sides of the river; they give the Upper Tapajoz its particularly attractive appearance. Since the best site for the establisment of a settlement is usually to be found just below the upper spur of each concave section of the river bank the topography had to be considered in the settling of this area. Also shown on the map is the lower course of the Cururu river, a righthand tributary of the Upper Tapajoz. The river is there nearly graded and as a result its course is meandering. During the rainy season the wide valley floor is completely flooded. Under these conditions the river shows a tendency to shorten its course. Many oxbow lakes indicate that a great number of meanders have been breached. During the dry season the river is confined to its narrow and winding bed. Settlements can only be established where the river in its meandering course touches the valley slope.